New networked technologies and carers of people with dementia: an interview study - Powell, J; Gunn, L; Lowe, P; Sheehan, B; Griffiths, F; Clarke, A (2010)
Dementia is one of the greatest contemporary health and social care challenges, and novel approaches to the care of its sufferers are needed. New information and communication technologies (ICT) have the potential to assist those caring for people with dementia, through access to networked information and support, tracking and surveillance. This article reports the views about such new technologies of 34 carers of people with dementia. We also held a group discussion with nine carers for respondent validation. The carers' actual use of new ICT was limited, although they thought a gradual increase in the use of networked technology in dementia care was inevitable but would bypass some carers who saw themselves as too old. Carers expressed a general enthusiasm for the benefits of ICT, but usually not for themselves, and they identified several key challenges including: establishing an appropriate balance between, on the one hand, privacy and autonomy and, on the other: maximising safety; establishing responsibility for and ownership of the equipment and who bears the costs; the possibility that technological help would mean a loss of valued personal contact; and the possibility that technology would substitute for existing services rather than be complementary. For carers and dementia sufferers to be supported, the expanding use of these technologies should be accompanied by intensive debate of the associated issues. Copyright © Cambridge University Press 2010.